Decomposing the foreclosure crisis: House price depreciation versus vad underwriting - Kristopher Gerardi; Adam Hale Shapiro; Paul S. Willen (Federal Reserve Bank of Atlanta, 2009)
We estimate a model of foreclosure using a data set that includes every residential mortgage, purchase-and-sale, and foreclosure transaction in Massachusetts from 1989 to 2008. We address the identification issues related to the estimation of the effects of house prices on residential foreclosures. We then use the model to study the dramatic increase in foreclosures that occurred in Massachusetts between 2005 and 2008 and conclude that the foreclosure crisis was primarily driven by the severe decline in housing prices that began in the latter part of 2005, not by a relaxation of underwriting standards on which much of the prevailing literature has focused. We argue that relaxed underwriting standards did severely aggravate the crisis by creating a class of homeowners who were particularly vulnerable to the decline in prices. But, as we show in our counterfactual analysis, that emergence alone, in the absence of a price collapse, would not have resulted in the substantial foreclosure boom that was experienced.
Keywords: D11; D12; G21; 330; foreclosure; mortgage; house prices; Zwangsvollstreckung; Subprime-Hypothek; Finanzmarktkrise; Immobilienpreis; Massachusetts